Treating Philadelphia chromosome/BCR‐ABL1 positive patients with Glivec (Imatinib mesylate): 10 years' experience at Patan Hospital, Nepal. (29th March 2017) - Kayastha, Gyan K.; Ranjitkar, Nora; Gurung, Radha; KC, Raj K.; Karki, Sanjit; Shrestha, Roshan; Thapa, Raj K.; Rajbhandari, Piyush; Poudyal, Buddhi; Acharya, Paras; Roberts, David J.; Hayes, Bruce; et al.
Summary: The Glivec International Patient Assistance Programme makes Glivec (Imatinib mesylate) available to Philadelphia chromosome/BCR‐ABL1 positive patients with chronic myeloid leukaemia (CML) in Lower and Middle Income Countries (LMIC). We have established a large cohort of 211 CML patients who are eligible for Imatinib, in Kathmandu, Nepal. Thirty‐one patients were lost to follow‐up. We report on 180 CML patients with a median age of 38 years (range 9–81). Of these 180 patients, 162 underwent cytogenetic testing and 110 were investigated by reverse transcription polymerase chain reaction. One hundred and thirty‐nine of the 180 patients (77·2%) had at least one optimal response. Taken together, our cohort has a 95% overall survival rate and 78% of the patients were still taking Glivec at a median time of 48·8 months (range 3–140 months). The number of patients who actually failed therapy, as defined by the LeukaemiaNet 2013 criteria, was 39 (21·7%). While our cohort has some differences with those in North America or Europe, we have shown Glivec is effective in inducing an optimal response in our patients in Nepal and that it is possible to deliver a clinical service for CML patients using tyrosine kinase inhibitors in resource‐poor settings.